2019
DOI: 10.1063/1.5051630
|View full text |Cite
|
Sign up to set email alerts
|

Solution effect on improved structural compatibility of NiTi-based alloys by systematic first-principles calculations

Abstract: The functional stability of a shape memory alloy (SMA) may be related to its structural compatibility between the parent-phase and the martensitic-phase structures. In this study, we perform systematic first-principles calculations for 276 Ni-Ti-based ternary alloys to investigate their energetic stability as well as their structural compatibility between the parent-and the martensitic-phase structures. We analyze in detail the dependences of the energetics and structural properties on the additional element X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Haskins and Lawson [19] investigated the temperature-dependent thermodynamic properties of NiTi alloys by density functional theory molecular dynamics (DFT-MD), and then analyzed the finite temperature properties of three phases (ground state monoclinic B33, martensitic B19', and austenitic B2), and the results revealed that the anharmonic effects played a large role in both stabilizing the austenite B2 phase and suppressing the martensitic phase transition. By first-principles calculations, Lee et al [20] found that the functional stability of the SMA may be related to its structural compatibility between the parent-phase and the martensitic-phase structures, and the ternary NiTi-X alloys tended to have better structural compatibility than the binary equiatomic NiTi alloys, indicating that the functional stability of NiTi SMAs can be effectively improved by alloying additional elements. Liu et al [21] also utilized the systematic ab-initio simulations to explore the high-pressure behavior of NiTi SMAs at zero temperature and found that the known B19 phase was dynamically unstable, and an orthorhombic structure and a face-centered-cubic B32 structure became stable above ∼4 and 29 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Haskins and Lawson [19] investigated the temperature-dependent thermodynamic properties of NiTi alloys by density functional theory molecular dynamics (DFT-MD), and then analyzed the finite temperature properties of three phases (ground state monoclinic B33, martensitic B19', and austenitic B2), and the results revealed that the anharmonic effects played a large role in both stabilizing the austenite B2 phase and suppressing the martensitic phase transition. By first-principles calculations, Lee et al [20] found that the functional stability of the SMA may be related to its structural compatibility between the parent-phase and the martensitic-phase structures, and the ternary NiTi-X alloys tended to have better structural compatibility than the binary equiatomic NiTi alloys, indicating that the functional stability of NiTi SMAs can be effectively improved by alloying additional elements. Liu et al [21] also utilized the systematic ab-initio simulations to explore the high-pressure behavior of NiTi SMAs at zero temperature and found that the known B19 phase was dynamically unstable, and an orthorhombic structure and a face-centered-cubic B32 structure became stable above ∼4 and 29 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%